Effectiveness and prescription pattern of lipid-lowering therapy and its associated factors among patients with type 2 diabetes mellitus in Malaysian primary care settings - Elnaem, Mohamed Hassan Abdelaziz; Nik Mohamed, Mohamad Haniki; Zaman Huri, Hasniza; Mohd Shah, Azarisman Shah (Dove Medical Press, 2019)
Background: Cardiovascular diseases (CVDs) are the main complication leading to morbidity and mortality among patients with type 2 diabetes mellitus (T2DM). There is a large amount of evidence to support the use of lipid-lowering therapy (LLT) for the prevention of CVD. This study aimed to assess the effectiveness and prescription quality of LLT among T2DM patients and to identify its associated factors.